Enhanced Supercapacitor Performance of N‐Doped Mesoporous Carbons Prepared from a Gelatin Biomolecule. Issue 8 (26th March 2013) - Dhawale, Dattatray S.; Mane, Gurudas P.; Joseph, Stalin; Anand, Chokkalingam; Ariga, Katsuhiko; Vinu, Ajayan
<x xml:space="preserve">Abstract</x> Nitrogen‐containing mesoporous carbon electrodes with tunable pore diameters for supercapacitor applications are synthesized by the nanocasting technique using a naturally abundant gelatin polymer as the single precursor for nitrogen and carbon.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>